Integrating statistical writing in an applied regression course using small-scale writing projects - Laura A. Hildreth; Ella M. Burnham (Journal of Statistics and Data Science Education, 2025)
Effective communication skills, both written and oral, are considered core skills for statisticians. This article presents five small-scale writing projects that were developed for an applied regression course, including the specific writing skills emphasized in each project and what each project entails. We also present and discuss results from surveys on changes in writing attitudes throughout the course and student feedback on the projects. The results indicate improved attitudes toward writing and a positive experience for students. Recommendations for incorporating the writing projects based on our observations of implementing them and potential changes are also provided. Materials for all projects are available in the online supplemental materials.